Comparing Poverty in 13 OECD Countries Traditional and Synthetic Approaches - Michael Förster (Luxembourg Income Study (LIS), 1993)
A comprehensive look not only into the poverty rankings but the methodology used to gain them. Special attention and is paid to the unit of economic analysis, choice of equivalence scale, and selection of approach to define and measure poverty. The role of the state in alleviating poverty is also investigated.
Keywords: 330